Techniques for improving response rates in OM survey research - Frohlich, Markham T (Journal of Operations Management, 2002)
AbstractResponse rates are an important indicator of survey research success and a methodological concern in OM today. An analysis was done of 233 OM survey research papers published over the past 12 years which showed that the average managerial response rate flattened‐out in the mid‐1990s at, approximately 32% and has not improved since then. This paper goes on to examine the theories and techniques found in the diverse survey research literature on improving response rates including OM survey research benchmarks that achieved very high response rates. By following the tactics outlined in this paper, OM survey researchers stand an excellent chance of not only improving the overall respondent yields for their studies but also reducing the bias caused by non‐response.